2023
DOI: 10.1002/cncr.34934
|View full text |Cite
|
Sign up to set email alerts
|

Social isolation and social connectedness among young adult cancer survivors: A systematic review

Rina S. Fox,
Grace E. Armstrong,
Julia S. Gaumond
et al.

Abstract: BackgroundSocial isolation and connectedness are social determinants of health that have demonstrated effects on cancer‐related outcomes. These constructs have been systematically evaluated among pediatric and older adult cancer populations. In this review, the authors evaluated the prevalence, correlates, and psychosocial implications of social isolation and connectedness among young adult (YA) cancer survivors aged 18–39 years.MethodsPeer‐reviewed articles published in English before June 2021 were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 108 publications
1
15
0
Order By: Relevance
“…Adolescents who reported more social connectedness pre-COVID-19 had lower depression symptoms and higher mental health one year post COVID-19, compared to adolescents reporting lower social connectedness, suggesting that engaging with close ones and establishing a sense of community may serve as protective factors amid physical distancing 143 . A recent review suggests that social isolation is associated with worse psychological well-being, supporting the notion that interactions that maintain or support relationships with close ones may be especially useful in reducing stress, thereby reducing disease susceptibility 144 .…”
Section: Discussionmentioning
confidence: 90%
“…Adolescents who reported more social connectedness pre-COVID-19 had lower depression symptoms and higher mental health one year post COVID-19, compared to adolescents reporting lower social connectedness, suggesting that engaging with close ones and establishing a sense of community may serve as protective factors amid physical distancing 143 . A recent review suggests that social isolation is associated with worse psychological well-being, supporting the notion that interactions that maintain or support relationships with close ones may be especially useful in reducing stress, thereby reducing disease susceptibility 144 .…”
Section: Discussionmentioning
confidence: 90%
“…Social connectedness is posited to serve as a buffer against psychological distress, enhancing individuals' ability to regulate their emotions and reduce engagement in risktaking behaviors. This protective role is supported by evidence indicating that strong social ties can mitigate the impact of stressors on mental health and promote resilience (Fox, 2023;Ransome, 2023).…”
Section: Introductionmentioning
confidence: 90%
“…Lim (2023) reported that social connectedness significantly enhances health outcomes in older adults, emphasizing its role in emotional well-being (Lim, 2023). Moreover, the detrimental effects of social isolation on mood and mental health further affirm the critical role of social connectedness in psychological functioning (Fox, 2023).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…For instance, Stam, Grootenhuis, and Last (2005) found that childhood cancer survivors had fewer friends and spent less time in relationships with peers than the comparison population. About the young adult population, a review by Fox et al (2023) found that cancer survivors who experienced social isolation were also at risk of mental health issues. Conversely, social support was positively linked to post-traumatic growth and negatively associated with anxiety, depression and psychological distress (Deegan, Brennan, Gallagher, Lambert, & Dunne, 2023).…”
Section: Introductionmentioning
confidence: 99%